Spring and summer time ozone and solar ultraviolet radiation variations over Cape Point, South Africa - (:unkn) unknown (My University, 2019)
The correlation between solar ultraviolet radiation (UV) and atmospheric ozone is well understood. Decreased stratospheric ozone levels which led to increased solar UV radiation levels at the surface have been recorded. These increased levels of solar UV radiation have potential negative impacts on public health. This study was done to determine whether the break-up of the Antarctic ozone hole has an impact on stratospheric columnar ozone (SCO) and resulting ambient solar UV-B radiation levels at Cape Point, South Africa, over 2007–2016. We investigated the correlations between UV index, calculated from ground-based solar UV-B radiation measurements and satellite-retrieved column ozone data. The strongest anti-correlation on clear-sky days was found at solar zenith angle 25∘ with exponential fit R2 values of 0.45 and 0.53 for total ozone column and SCO, respectively. An average radiation amplification factor of 0.59 across all SZAs was calculated for clear-sky days. The MIMOSA-CHIM model showed that the polar vortex had a limited effect on ozone levels. Tropical air masses more frequently affect the study site, and this requires further investigation.
Keywords: African Research